A MONOGRAPHIC REVISION OF THE GENUS PODOCARPUS (PODOCARPACEAE): I. HISTORICAL REVIEW. (7th November 2014) - Mill, R. R.
<x content-type="archive" xml:space="preserve">Abstract</x> The taxonomic history of the genus Podocarpus (Podocarpaceae) is reviewed as the first part of a revision of the genus. The major taxonomic and other works relating to the genus published during nine time periods (before 1800, 1800–1850, 1851–1875, 1876–1900, 1901–1926, 1927–1947, 1948–1967, 1968–1987 and 1988–present) are briefly but critically discussed. Three landmark works are those by Pilger (1903), Buchholz and Gray (between 1948 and 1962) and de Laubenfels (1985). The paper ends with an outline plan of the revision of the genus to which the paper forms an introduction.